A case of widespread unilateral subcutaneous sarcoidosis with ocular and pulmonary involvements with seropositivity for anti‐double strand‐DNA antibody and rheumatoid factor: A revisit of gap between humoral autoimmune abnormalities and clinical findings - Noritaka Oyama; Natsuki Baba; Hideki Ido; Minoru Hasegawa (Frontiers Media S.A., 2022)
We present a middle‐aged female Japanese case of subcutaneous sarcoidosis on the unilateral limb with pulmonary and eye involvements, who was seropositive for anti‐double strand DNA antibody and rheumatoid factor. The oculocutaneous and pulmonary lesions were subsided with persisted serological abnormalities. This paper provides updating evidence for the pathogenic significance of humoral autoimmune background in the disease.